Metro liminal painting liminal spaces to resist transience and feelings of surveillance - Aypa, Gillian A.; Romero, Riza A.; Mangila, Dominic (Quezon City College of Fine Arts, University of the Philippines Diliman, 2022)
Metro Liminal explores painting liminal spaces that serve as comfort form the feelings of surveillance from dominant spaces and painting them to confront the transitory nature of places of passsage.

The transience of liminal spaces does not allow one to linger in them, hence, photographs are used reference to capture fleeting moments of travel through places of passage. The unnoticed spaces depicted in paintings such as parking lot in SM North, LRT train platform, and staircase in UP University Theater provides solitude and comfort because we identify with these peripheral spaces. Several theories and concepts on liminality are used such as Arnold van Gennep's liminal period or transition to interpret the pandemic effect on spaces and the resumption of human activity in public spaces; Marc Augè's non-places as generic liminal spaces that allow feelings of solitude despite movement and transience; and Rick Iedema, Debbi Long, and Katherine Carrol's microgeographies of social life or mundane liminal spaces.

This thesis contributes to understanding liminal spaces as overlooked and peripheral spaces that offer solitude and comfort. It also opens further studies on liminal spaces from different perspectives such as class, gender, and demographics.
Thesis (Bachelor of Fine Arts in Painting)
Bibliography: leaves 32-33
Keywords: Liminality -- Philippines; Public spaces -- Philippines; Photography of painting